Legal Politics of Holding Simultaneous Regional Elections in 2024 (Portrait of Political Party Debate in Parliament) - Priyanto, Eka; Haikal Mubarak; Mardiansah, Songgi; Bunyamin, Bubun; Permana, Diki (Formosa Journal of Sustainable Research, 2024)
The resolution of simultaneous regional elections through a political-legal process in parliament is the subject of complex and crucial debate in the context of local democracy in Indonesia. This article describes the dynamics of legal politics and a portrait of the debate between political parties in parliament regarding regulations for simultaneous regional elections. Through in-depth analysis, this article explains the factors that influence the position and strategy of political parties in influencing regulations, as well as their impact on the results of debates in parliament. Conclusions and suggestions are offered to increase the effectiveness of the simultaneous regional election resolution process and strengthen local democracy in Indonesia